Pemberdayaan Masyarakat Desa Bunyu Kalimantan Utara melalui Pelatihan Budidaya Hidroponik: Empowering the Bunyu Village Community, North Kalimantan through Hydroponic Cultivation Training - Nurhasanah, Nurhasanah; Yuniar, Dewi; Anggraini, Ike; Dewi, Ratna Fitriana; Gunawan, Muhammad Tigo; Suprapto, Suprapto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Hydroponics is cultivating plants in a nutrient solution, producing plants with a higher yield, quality, taste, and nutritional value than plants grown in soil. Another advantage of the hydroponic cultivation technique is that it does not require large land and can save water use. Therefore, this technique is very suitable to be applied to areas with limitations on productive agricultural land and freshwater, such as Bunyu Island. A hydroponic cultivation training program on Bunyu Island, Bulungan Regency, North Kalimantan Province, aims to empower the community to produce vegetables independently and increase income and welfare. The empowerment program was carried out, starting with socialization, training, mentoring, and program evaluation. The results showed that the characteristics of the community empowerment program participants were dominated by housewives (60%) with an educational background of high school graduates/equivalent (60%), with an age range of 27-58 years. The public perception of hydroponic is easier to maintain, does not require large areas of land, is more resistant to pests and plant diseases, has no weeding, has better harvest quality, and has higher selling prices than conventionally cultivated vegetables. This shows that the community already has the correct understanding of hydroponics. The community empowerment through the hydroponics program in Bunyu Village increased community enthusiasm and interest in hydroponic cultivation to obtain and consume vegetables easily and as a source of family economic income.